Comparison the Hydraulic Harvested Energy with the Electromagnetic Systems and the Spent Energy on the Active System - Dinar, Murtadha Q.; Abid, Haider J.; Khalaf, Hassanein I. (Basrah Journal for Engineering Sciences, 2022)
An energy-harvesting hydraulic regeneration suspension system is described in this article, which includes a hydraulic motor, a spool valves, and a hydraulic cylinder. Regenerative actuators are built using a hydraulic transmission system as their inspiration. The proposed regenerative actuator is implemented in the vehicle’s non-linear suspension system for a complete model. MATLAB Simulink is utilized to generate and simulate the entire vehicle’s regenerative suspension system, which has force properties which are nonlinear with hydraulic actuators equations with energy harvesting from regenerative actuators. During the mathematical simulation, the effect of pressure differential on the spool valve’s operation is also taken into account. The quantity of captured energy is compared to the energy expended on the active actuator and the energy generated with the electromagnetic actuator at three distinct input signals at three different pressure level (10, 30 and 50 bars) (random, sinusoidal, and square). The energy generated in the regenerative hydraulic actuator at three pressure levels behaves the same as the active actuator in terms of response, plus the highest pressure of 50 bar is closely comparable to the active system in terms of energy harvest and gradually decreases as the output pressure drops in addition to the behavior of the electromagnetic and its comparison with the wasted energy of the active system.